Study of the Social Acceptance and Self-Esteem Levels of High School Students Who Do Sports towards Disabled Students - Dalbudak, İbrahim (2021)
Education is everyone’s right. This right has been emphasized in many national and international legal texts. Based on this fact, it is extremely important to consider the fact that disabled individuals also have equal rights arising from citizenship as a social acceptance and self-esteem principle. In this sense, social acceptance and self-esteem levels of students who fulfill the special aims of education and do sports towards the students with disabilities emerge as an important issue. Therefore, the aim of this study is to examine the possible relationship between social acceptance and self-esteem levels of different high school students who do sports towards the students with disabilities in Turkey. In this study including high school students doing sports, Social Acceptance Scale and Coopersmith Self-Esteem Inventory were used to evaluate various variables of students towards disabled students. “Mann Whitney U” and “Kruskal Wallis 1 Way ANOVA” tests were used in the analysis of the scores obtained from the research scales of the students. Also, social anxiety results were determined by using the “Dunn’s Nonparametric Comparison” test for significant differences. Kolmogorov-Smirnov (KS) and Shapiro-Wilk (SW) tests were used to examine the Coopersmith self-esteem inventory and its sub-dimensions.  There is no statistically significant difference between the total score averages of the social acceptance and subscales of the students according to their age, gender, number of siblings, father and mother’s education (p > .05). Social acceptance scale total score averages of students differ according to sports branches (p < .05). Students’ Coopersmith self-esteem inventory and subscale total mean scores do not differ according to age, gender, number of siblings, income levels of their families, and educational status of the mother and father (p > .05). Students’ Coopersmith self-esteem inventory and subscale total scores differ according to sports branches (p < .05). There is no statistically significant relationship between students’ “social acceptance scale” and “coopersmith self-esteem inventory” (p > .05). According to the data obtained from this study, we can say that sports affect the emotions and thoughts of the students, and this has a positive attitude towards disabled students in the classroom. Sport enables individuals to socialize. Regardless of the type of disability, we can say that every individual is valuable for athletes. Sport is brotherhood. Students who play sports can empathize. By directing our students to sports branches according to their abilities, we can change their feelings and thoughts towards disabled people and as a society, we can be more sensitive to disabled people.